The Effect of Using Digital Marketing Tools in Consumer Behavior: A Field Study on Consumers of Perfumes and Cosmetics in Latakia City (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The study aimed to examine the impact of using digital marketing tools on consumer behavior among perfume and cosmetics consumers in the city of Latakia. This was achieved by focusing on four main digital marketing tools: websites, email marketing, social media platforms, and paid digital campaigns, in addition to analyzing consumer behavior through its three dimensions: satisfaction, loyalty, and word of mouth. The study adopted the descriptive analytical approach. To achieve the research objectives, a questionnaire was designed based on a five-point Likert scale and distributed to a random sample of perfume and cosmetics consumers in Latakia city. A total of (380) valid questionnaires were obtained for statistical analysis. The collected data were then analyzed using appropriate statistical methods. The results revealed that the level of use of digital marketing tools by perfume and cosmetics organizations, from the perspective of their customers, was moderate, with noticeable variation among the tools. Social media platforms and paid digital campaigns recorded high levels of use, while websites and email marketing showed moderate levels tending toward low usage. Furthermore, the findings indicated that consumer behavior was at a high level, with the dimensions of satisfaction, loyalty, and word of mouth all showing strong positive levels. The results also demonstrated a statistically significant positive impact of digital marketing tools on consumer behavior, with variation in the strength of impact among the tools. Paid digital campaigns ranked first, followed by social media platforms, then email marketing, and finally websites.
Keywords: Digital marketing tools, consumer behavior, social media, website, email marketing, paid digital campaigns.